1995
DOI: 10.1541/ieejpes1990.115.5_487
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Fuzzy Logic Control between SVC and PSS to Enhance Stability of Power Systems

Abstract: SUMMARYThis paper presents a new switching control scheme for static var compensator (SVC) using fuzzy logic control rules to enhance the overall stability of electric power systems. In addition, the coordination with power system stabilizers (PSS) is also considered to achieve a wider stable region. An SVC is set on one of the busbars in the transmission system, where the real power flow signal is utilized at the location of the SVC to determine the firing angle of the thyristor switch. The switching control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…An alternative way is to implement different control law according to different operating conditions, i.e. to develop an event driven control strategy [4,5]. This implies that a hybrid control strategy, which is an integration of the numerical and heuristic approaches, is needed.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…An alternative way is to implement different control law according to different operating conditions, i.e. to develop an event driven control strategy [4,5]. This implies that a hybrid control strategy, which is an integration of the numerical and heuristic approaches, is needed.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The voltage deviation ⌬U s , the speed deviation ⌬ o and the deviation of acceleration ⌬ o are adopted as input variables, and the variation of the control angle ⌬␦ i is used as the output variable of the controller. According to Hiyama et al [2][3][4], a point p(k) in the phase plane (as shown in Fig. 4) can give the system condition at a particular instant t = k⌬t.…”
Section: Multi-objective Hybrid Fuzzy Controllermentioning
confidence: 99%
See 3 more Smart Citations